Exploring the Landscape: Israel Studies in Non-Western Contexts. - Zeedan, Rami; Tsurumi, Taro; Jangid, Khinvraj; McGonigle, Ian; Gherman, Michel (Israel Studies)
As the field of Israel Studies continues to evolve and gain prominence in academic circles, it is crucial to examine its status beyond its traditional places of growth in North America, Europe, and Israel. This roundtable brings together a diverse group of experts to explore the current state of Israel Studies globally. It offers diverse insights into the unique challenges, opportunities, and contributions emerging from their positionalities. This comprehensive discussion of Israel Studies beyond the traditional Western context explores how scholars, institutions, and communities engage with and contribute to the field in regions marked by distinct geopolitical, cultural, and historical conditions.